2017
DOI: 10.1186/s13690-017-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Using the World Health Organization health system building blocks through survey of healthcare professionals to determine the performance of public healthcare facilities

Abstract: BackgroundAcknowledging the health system strengthening agenda, the World Health Organization (WHO) has formulated a health systems framework that describes health systems in terms of six building blocks. This study aimed to determine the current status of the six WHO health system building blocks in public healthcare facilities in Ethiopia.MethodsA quantitative, cross-sectional study was conducted in five public hospitals in central Ethiopia which were in a post-reform period. A self-administered, structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 29 publications
6
117
0
Order By: Relevance
“…Thirdly, our research confirms findings from previous studies about the negative effect of structural barriers, such as shortages of surgical essentials, on the provision of surgical care in low and middle income countries . Our study suggests that by improving skills, confidence, attitudes and motivation of local surgical teams, supportive supervision can contribute to mitigating some of the structural barriers at rural district hospitals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thirdly, our research confirms findings from previous studies about the negative effect of structural barriers, such as shortages of surgical essentials, on the provision of surgical care in low and middle income countries . Our study suggests that by improving skills, confidence, attitudes and motivation of local surgical teams, supportive supervision can contribute to mitigating some of the structural barriers at rural district hospitals.…”
Section: Discussionsupporting
confidence: 88%
“…It is part of the essential package of services needed to achieve universal health coverage (UHC) . As such it is an indicator of how close or far a country is from achieving UHC ; and, if high coverage can be achieved, can help drive the delivery of comprehensive UHC . Yet, despite consensus that access to surgical services on a global scale is required (WHA Resolution 68.15) , 5 billion people do not have access to safe, affordable surgical and anaesthesia care when needed .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the studies con rmed that the PHC in Iran at a local-organizational structure faces some problems in responding to new population needs, which gradually weaken the system [21]. The PHC in Iran has some challenges and weaknesses that oblige structural reforms [22,23]. Malekafzali argued that we are concerned about the diminished monitoring of PHC due to the high employment of the head of the university and his deputies [11].…”
Section: Leadership and Governancementioning
confidence: 99%
“…Regarding the workforce employed at the PHC, the results of this study indicated that paying for the PHC personnel is not related to the way services are provided. Some studies suggested that there are different payment models in Iranian health system and the current payment system should be improved [22,23,28] The payment system to the service provider in PHC Iran has not been favorable and it is not an incentive to improve performance, quality and performance for them [21]. In addition, the studies con rmed that ine ciencies in the public governmental system and administrative costs were accompanied by a lack of PHC resources [25].…”
Section: Health Care Nancingmentioning
confidence: 99%
See 1 more Smart Citation